Identifikasi dan Potensi Cendawan Indigenous untuk Pelapukan Batang Kelapa Sawit di Bogor, Indonesia - Nofrifaldi; Hariyadi; Widyastuti, Rahayu (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Indigenous microorganisms effectively accelerate the decomposition of agricultural waste and agricultural waste that has been decomposed properly can be an organic fertilizer containing macro and microelements. The aim of the study was to determine the potential of indigenous cellulolytic fungi in the palm oil stems after replanting. The research was conducted at the Cikabayan Experimental Field Bogor Agricultural University, Dramaga, West Java. The experiment was conducted in October 2018 until January 2019, using a randomized complete block design consisting of four decomposition methods treatment: control, added with decomposer, chopping, and chopping+decomposer. The results showed that four isolates and isolate A were chosen to calculate the number of fungi at a dilution rate of 10-6 because they had the largest diameter. The identification results of isolate A were Trichoderma harzianum fungi and it was concluded that Trichoderma sp. in the palm oil stem after replanting, it has the potential as an indigenous cellulolytic fungus of oil palm trunks. The chopping+decomposer treatment can accelerate the weathering of the oil palm stem with a significant influence between the treatments that have met the requirements of compost maturity as specified in SNI 19-7030-2004 with ratio C/N 16.11 at 3 months after treatment. Keywords: decomposer, Elaeis guineensis Jacq., isolate, Trichoderma sp.